Estructura comunitaria de la ictiofauna bentónica en el delta del Orinoco y Golfo de Paria (Venezuela), 50 años después de la construcción del dique del caño Manamo (2016)
To evaluate the impacts of water flow restriction and regulation caused by the construction of a dike across Manamo Channel, variations in the benthic fish communities were studied in the mouths of three streams (Pedernales, Angostura and Manamo) of the Orinoco River Delta and one stream (Venado) that flows directly into the Gulf of Paria, during one (annual) hydrological cycle. Fishes were sampled with a shrimp trawl net. Of the 78 species collected, five were resident, 12 temporary and 62 occasional. Juvenile phases of all species were collected. Species with greater IVI values were Cathorops sp., Achirus achirus, Stellifer naso and Colomesus psittacus. No significant differences were obtained for the physical and chemical habitat parameters measured: depth, salinity and transparency, nor in the water levels of the streams even in different hydro-phases of the year. Salinity never dropped to zero and no changes in fish species composition were detected. These results lead us to hypothesize that the impacts of the dike constructed in Manamo Channel also extend to other streams of the Orinoco River Delta and even the one studied (Venado) that empties into the Gulf of Paria, where estuarine conditions prevailed during the entire study period of one year, with no observed changed in the hydrological regimen.